Identifying vehicles as green cars using Q methodology: Viewpoints of Korean transport policy experts - Lee, Youhyun; Park, Minju (International Journal of Sustainable Transportation, 2023)
The recent trend of transitioning from cars with internal combustion engines to green cars has accelerated amidst growing concerns of a climate crisis and the COVID-19 pandemic. South Korea is a particularly good test bed for exploring green mobility alternatives and setting priorities for green car policies, owing to its fast-growing green car market and its considerable share in the worldwide purchases of fuel cell electric vehicles. Accordingly, this study explores the Korean conceptualization of green cars and the prioritization of different aspects of future green car policy using qualitative Q methodology and additional interviews. A total of 31 transport policy experts participated in our survey, resulting in three distinct perspectives: a hybrid vehicle supporter with comparative pragmatism, an electric vehicle supporter from multiple aspects, and a radical ecologist searching for new alternatives. Based on these expert insights, we determine the most appropriate green car type and provide important recommendations for future green car policy.
Keywords: Battery-electric vehicles; Fuel cell electric vehicle; Green car; Green mobility; Recent trends; South Korea; Sustainable transport; Sustainable transport policy; Test bed; Transport policy; Battery electric vehicle; fuel cell electric vehicle; green car; hybrid electric vehicle; sustainable transport policy